If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(y + -1) + 8 = 33 Reorder the terms: 6(-1 + y) + 8 = 33 (-1 * 6 + y * 6) + 8 = 33 (-6 + 6y) + 8 = 33 Reorder the terms: -6 + 8 + 6y = 33 Combine like terms: -6 + 8 = 2 2 + 6y = 33 Solving 2 + 6y = 33 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6y = 33 + -2 Combine like terms: 2 + -2 = 0 0 + 6y = 33 + -2 6y = 33 + -2 Combine like terms: 33 + -2 = 31 6y = 31 Divide each side by '6'. y = 5.166666667 Simplifying y = 5.166666667
| (3x-7)+(3x-1)=16 | | 23-4=y | | 4(-1)-4y=24 | | 4x^2-24x+10=0 | | -4k=3 | | y=-(2)+12 | | y=-(1)+12 | | -11r=-4r+5 | | y=-(0)+12 | | 2a+3=-2 | | 6(8)+3(-9.333333)=20 | | y=-(-1)+12 | | 3/5x-15=6/5x+12 | | 1/4x=6 | | 5=s/-7 | | 3/5a=3/5 | | 1/2(16v-96)=0 | | 3q-48=3q | | 230/125 | | 66/8+10=x | | x=-5+1.667y | | 3.5x+4=7.5 | | Y=3(x-1)(x-5) | | 2x+6=y | | y=8(2)-4 | | 5/8x+1/4=-7 | | x+8/2/3x+24/5 | | y=8(1)-4 | | y=8(0)-4 | | 6(8)-3(-9.3333333)=76 | | y=8(-1)-4 | | Y=-(x+3)-2 |